Edukasi Pembelajaran Al-Qur’an Jamaah Oemah Qur’an Soediyono dalam Progam Pemberantasan Buta Huruf Al-Qur’an di Sragen Tahun 2025-2026 - Erlita Kusuma Dewi; Nadhifa Nur Alifazahro; Reyhan Aditya Julianto; Adinda Cantika Rini; Triono Ali Mustofa (Universitas Pahlawan Tuanku Tambusai, 2026)
The phenomenon of Quranic illiteracy among the elderly remains an unresolved challenge in Indonesia. Inappropriate teaching methods and inadequate instruction result in lagging and inefficient use of time in reading and writing the Quran. The goal of this activity is to eradicate Quranic illiteracy among the elderly, especially at Oemah Quran Soediyono, Sragen. The methods used in the activity include community education and training, starting from planning, implementation, and evaluation. The results of the activity show that the Albirru learning method is proven to be effective, flexible, enjoyable, and oriented towards rapid results. Supporting factors for this program include the availability of adequate facilities and infrastructure with comfortable classrooms, digital media, and standard Quranic manuscripts. While inhibiting factors include frequent participant fatigue and decreased attendance. The resulting impact is that after one month, 85% of students had increased Quranic literacy, self-confidence, and involvement in mosque activities, concluding that this activity was successful.